Lokalitas Seni Kaligrafi Masjid di Minangkabau, Analisis Fungsi dan Makna - Aisyah, Siti; Hakim, Lukmanul; Yulniza, Yulniza; Rohaizat bin Abdul Wahab, Mohd (Jurnal Lektur Keagamaan, 2023)
ABSTRACT This article discusses the function and meaning of mosque calligra-phy in one of the Minangkabau regions, whose application changes its essential function and meaning because the mosque calligraphy was applied in line with the religious and cultural conditions of the people. The purpose of this research is to describe the function and meaning of the locality of the calligraphy of the community mosque in Padang Pariaman, one of the Minangkabau areas. Qualitative research design was employed, and the data was collected through observation, interviews,and documentation. The study found that calligraphy in mosques has function to not only beautifyingthe mosque, but also distinguishingMuslim houses of worship from other buildings,so that people do not make mistakes in writing. In addition, as a symbolof the religious identity of the mosque congregation, thewritten sentences symbolizing their religious understandingwere not always understood properly. Some community membersusedcalligraphies as amulet to cast away misfortune by putting them on the front door or main window of the mosque. This assumption occurs because they understand and interpret every Arabic letter as the art of calligraphy. The stylization or indentation of the Arabic letters determines the beauty of calligraphy writing. Therefore, the mosque's calligraphy is formed with functions and meanings that are patterned in line with the religious and cultural forms of the people. Keywords: Islam in Archipelago, Kelantan, Little Mecca, Malay. ABSTRAK Artikel ini membahas tentang fungsi dan makna seni kaligrafi masjid di salah satu wilayah Minangkabau yang penerapannya merubah fungsi dan maknanya dasarnya karena kaligrafi masjid diaplikasikan sejalan dengan kondisi keagamaan dan budaya masyarakatnya. Tujuan penelitian-nya untuk mengungkapkan fungsi dan makna lokaltitas dari kaligrafi masjid masyarakat di Padang Pariaman, salah satu wilayah rantau Minangkabau. Metode penelitian kualitatif dengan teknik mendapatkan data melalui observasi, interview dan dokumentasi. Hasil penelitian dite-mukan bahwa kaligrafi di masjid tidak hanya untuk memperindah masjid-nya tetapi untuk membedakan rumah ibadah umat Islam dengan bangunan lain sehingga tidak mempermasalahkan kekeliruan dalam penulisannya. Selain itu juga sebagai simbol identitas keagamaan jama’ah masjidnya yang terkesan tidak ada upaya menampilkan kalimat tulisan simbol paham keagamaanya dalam bentuk yang baik dan benar. Ada juga yang dijadikan sebagai pelindung dari malapetaka, dengan cara mengutamakan penulisan kalimat tersebut pada bagian depan atau jendelautama masjidnya. Anggapan tersebut terjadi karena mereka memahami setiap huruf Arab dimaknai dengan seni kaligrafi, dan keindahan penulisan kaligrafi dinilai dari stilasi atau bentuk lekukan dari huruf Arab tersebut, sehingga bentuk kaligrafi masjidnya terbentuk fungsi dan makna yang bercorak sejalan dengan bentuk keagaamaan dan budaya masyarakatnyaKata Kunci: Fungsi, Makna, Kaligrafi Masjid. Kata kunci: Islam di Nusantara, Kelantan, Mekkah Kecil, Melayu, Serambi Mekkah.